The Role of the Executive Branch in Latin American Constituent Processes - Aguirre, José Eduardo (USFQ Law Review, 2025)
The constituent power is the original force through which a society begins to organize itself by means of a document accepted for that purpose. Its importance lies both in the process that channels it and in the final result: a constitution. This document determines the structure of power, the recognition of rights, and the identity of the territory it governs. The risk of interference in its content through the imposition of a prevailing political agenda is considerable. Latin American experiences bear witness to this, which is why the ultimate outcome of this exceptional act must be rigorously analyzed. It is not enough for a constitution to be acclaimed by the people; it must also be deliberated by them